2001
DOI: 10.1042/bj3590295
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel class of insect glutathione S-transferases involved in resistance to DDT in the malaria vector Anopheles gambiae

Abstract: The sequence and cytological location of five Anopheles gambiae glutathione S-transferase (GST) genes are described. Three of these genes, aggst1-8, aggst1-9 and aggst1-10, belong to the insect class I family and are located on chromosome 2R, in close proximity to previously described members of this gene family. The remaining two genes, aggst3-1 and aggst3-2, have a low sequence similarity to either of the two previously recognized classes of insect GSTs and this prompted a re-evaluation of the classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
157
1
13

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(175 citation statements)
references
References 35 publications
4
157
1
13
Order By: Relevance
“…Lymphatic filariasis infects 120 million people in 73 countries worldwide and continues to be a worsening problem, especially in Africa and the Indian subcontinent 28 . Control of such diseases is becoming increasingly difficult because of increasing resistance to synthetic insecticides 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Lymphatic filariasis infects 120 million people in 73 countries worldwide and continues to be a worsening problem, especially in Africa and the Indian subcontinent 28 . Control of such diseases is becoming increasingly difficult because of increasing resistance to synthetic insecticides 29 .…”
Section: Introductionmentioning
confidence: 99%
“…They are involved in the detoxification of xenobiotics, protection from oxidative damage, isomerization, and intracellular transportation (Hayes and Pulford, 1995;Yu, 1996). In insects, cytosolic GSTs are classified into six classes, i.e., sigma, zeta, theta, delta, epsilon, omega, plus several unclassified genes (Ranson et al, 2001;Ding et al, 2003;Enayati, et al, 2005). Among them, the delta and epsilon classes, which are unique to insects, are involved in the xenobiotic metabolism (Ranson, et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In insects, cytosolic GSTs are classified into six classes, i.e., sigma, zeta, theta, delta, epsilon, omega, plus several unclassified genes (Ranson et al, 2001;Ding et al, 2003;Enayati, et al, 2005). Among them, the delta and epsilon classes, which are unique to insects, are involved in the xenobiotic metabolism (Ranson, et al, 2001). Most studies related to insect GSTs have emphasized their roles of detoxification and induction by allelochemicals, drugs, insecticides, and other xenobiotics (Yu, 1984;Kao et al, 1989;Fournier et al, 1992;Yu, 1999;Ranson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] It has been shown that the GST Epsilon class isoform 2 from A. gambiae (AgGSTE2) is associated to DDT resistance via two mechanisms: elevated gene expression and catalytic activity of the recombinant enzyme. 14 For this reason, AgGSTE2 is overexpressed in resistant strains and the recombinant protein is efficient at metabolizing DDT. 14,15 Furthermore, we have previously sequenced six new GSTE members in three species of Anopheles, and shown that the GSTE2 gene displays the highest level of conservation among all the GSTEs in the four Anopheles species.…”
Section: Introductionmentioning
confidence: 99%